2019
DOI: 10.18805/ajdfr.dr-127
|View full text |Cite
|
Sign up to set email alerts
|

Investment challenges in milk sector (Case of a dairy factory in southwest of Algeria): Development prospects

Abstract: In this work, we are interested in studying the investment challenges of packaged reconstituted milk production in Southwest of Algeria. To reach this objective, we have calculated the cost price of two products (pasteurized milk and fermented milk) which present the main production line of the dairy factory of Bechar, to assess the profitability of the company. The cost price of milk was calculated from the general balance that shows all the movements of the accounts which we have esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…The contamination of milk by pathogenic microorganisms namely Staphylococcus spp, Salmonella spp and Listeria spp is a possible sign of one (Rainard and Poutrel, 1993;Feknous et al 2018;Benyagoub, 2018;Benyagoub, 2019): -Direct contact of the udders with dirty soil (wounds, unwashed udders before milking).…”
Section: Pathogenic Bacterial Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contamination of milk by pathogenic microorganisms namely Staphylococcus spp, Salmonella spp and Listeria spp is a possible sign of one (Rainard and Poutrel, 1993;Feknous et al 2018;Benyagoub, 2018;Benyagoub, 2019): -Direct contact of the udders with dirty soil (wounds, unwashed udders before milking).…”
Section: Pathogenic Bacterial Strainsmentioning
confidence: 99%
“…After 2 days of storage, the test sample revealed a maximum load of 2,3 Log 10 CFU/mL, then a decrease in this bacterial load was noted. However, no contamination was revealed by the pathogenic strains Salmonella spp and Listeria monocytogenes.The contamination of milk by pathogenic microorganisms namely Staphylococcus spp, Salmonella spp and Listeria spp is a possible sign of one(Rainard and Poutrel, 1993;Feknous et al 2018;Benyagoub, 2018;Benyagoub, 2019): -Direct contact of the udders with dirty soil (wounds, unwashed udders before milking).-Non-compliance with hygienic practices during milking at the farm level. -Mastitis infection.-The person who practices milking may be the carrier of a disease that can contaminate the milk (oronasal sphere, skin, wounds).…”
mentioning
confidence: 99%
“…Furthermore, stagnant water is a significant source of microbiological contamination (Benyagoub et al ., 2018). Indeed, the log-linear analysis in our study showed that the non-conformity rate for coliforms was 2.1 times higher in samples with freezing point above −0.530°H (16.67%) compared to samples with regular freezing point (7.59%).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we must focus on two essential points: First, the regeneration of the saturated adsorbent during the scaling-up by moving from the laboratory stage to the industrial scale, which can be considered as waste and its disposal, cannot be an economical option. This may include chemical, biological, or thermal way as practical methods, and according to El-Naas and Alhaija (2011), the most common methods consist of temperature changes (thermal swing adsorption) and changes in pressure (pressure swing adsorption); Second, the studied dairy industry should establish a program to limit the volume and pollutant load of discharged dairy effluents (Hamdani et al 2005;Benyagoub 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It includes an administrative block, a manufacturing workshop with two cold rooms and a steaming room, three collection basins for liquid effluents from the industry. The dairy unit has initially generated 31 direct jobs and as many other indirect jobs in the form of contracts (Benyagoub et al 2018a;Benyagoub 2019;Nabbou et al 2020).…”
Section: Dairy Effluents Characterizationmentioning
confidence: 99%